2016
DOI: 10.1142/s1363919616500250
|View full text |Cite
|
Sign up to set email alerts
|

Innovation Success in the Context of Inbound Open Innovation

Abstract: The concept or paradigm of open innovation has gained more and more attention over the last couple of years. Firms see open innovation nowadays as an important capability to build and maintain innovativeness, even in dynamic global markets. Nevertheless, there is still a lot of uncertainty regarding the question which factors determine successful innovation within the open innovation environment. In this regard, based on the dynamic capabilities view, we hypothesise that a firm’s openness, its absorptive capac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 113 publications
1
10
0
Order By: Relevance
“…These results are similar to those reported in previous research, which, in general terms, found a positive effect of AC on innovation performance (e.g., Escribano et al, 2009;Nitzsche, Wirtz, & Göttel, 2016). More specifically, with regards to Hypothesis 3 on the influence of potential AC, results confirm its positive effect, suggesting that it is worth investing in processes and routines that facilitate greater recognition and assimilation of external knowledge to enhance radical innovation.…”
Section: Discussionsupporting
confidence: 90%
“…These results are similar to those reported in previous research, which, in general terms, found a positive effect of AC on innovation performance (e.g., Escribano et al, 2009;Nitzsche, Wirtz, & Göttel, 2016). More specifically, with regards to Hypothesis 3 on the influence of potential AC, results confirm its positive effect, suggesting that it is worth investing in processes and routines that facilitate greater recognition and assimilation of external knowledge to enhance radical innovation.…”
Section: Discussionsupporting
confidence: 90%
“…The findings enable a fluent progress of the innovation project and support organizational learning, but only if the firm has an ability to utilize external knowledge (Rosell, 2014). To foster two-way information transfer, organization-wide positive attitudes toward external knowledge and its sharing are necessary (Nitzsche et al, 2016;Rosell, 2014), in addition to trust. As the motivations for collaboration may not always be reciprocal, both the buyer and the supplier need to understand why the cooperation is taking place and what advantages are expected.…”
Section: Article I: Stimulating Supplier Innovation In a Complex And mentioning
confidence: 92%
“…Although criticized as being "old wine in new bottles" (Christensen et al, 2005;Trott & Hartmann, 2009), and lacking a consistent theory (Gassmann et al, 2010), the emerging interest in new ideas and collaboration technologies makes the topic relevant (Remneland-Wikhamn et al, 2011). Consequently, academic research in the field of open innovation has rapidly increased over the last years (Linton, 2012;Nitzsche et al, 2016).…”
Section: Opening the Process Of Innovationmentioning
confidence: 99%
See 1 more Smart Citation
“…Absorptive capacity defined as the ability of an organization to recognize the value of external knowledge, assimilate it and use for commercial ends [28] is often used by researchers in explaining open innovation [52]. It is associated with both inbound and outbound OI practices [61] [62] [63]. Zahra & George (2002) argue that potential absorptive capacity comprising knowledge acquisition and assimilation and realized absorptive capacity that include transformation and exploitation are capabilities built upon each other to produce dynamic organizational capabilities in order to enhance innovation performance.…”
Section: Extant Literature On the Relationship Between Open Innovatiomentioning
confidence: 99%